2010
DOI: 10.3102/0002831210370711
|View full text |Cite
|
Sign up to set email alerts
|

Is the Supply of Mathematics and Science Teachers Sufficient?

Abstract: This study seeks to empirically ground the debate over mathematics and science teacher shortages and evaluate the extent to which there is, or is not, sufficient supply of teachers in these fields. The authors' analyses of nationally representative data from multiple sources show that math and science are the fields most difficult to staff, but the factors behind these problems are complex. There are multiple sources of new teachers; those with education degrees are a minor source compared to those with degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
150
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(160 citation statements)
references
References 25 publications
0
150
0
1
Order By: Relevance
“…As mentioned earlier, we have found that one negative consequence of teacher turnover is its important but often overlooked role in teacher shortages (Ingersoll, 2011;Ingersoll & Perda 2010). Turnover is a major factor behind the problems that many schools have staffing their classrooms with qualified mathematics, science, and other teachers.…”
Section: Trend 7: Less Stablementioning
confidence: 52%
See 2 more Smart Citations
“…As mentioned earlier, we have found that one negative consequence of teacher turnover is its important but often overlooked role in teacher shortages (Ingersoll, 2011;Ingersoll & Perda 2010). Turnover is a major factor behind the problems that many schools have staffing their classrooms with qualified mathematics, science, and other teachers.…”
Section: Trend 7: Less Stablementioning
confidence: 52%
“…We have explored this issue in depth elsewhere (see Ingersoll & Perda, 2010;Ingersoll, 2011). Among other findings, our data analyses show that, contrary to conventional wisdom, the growth in the new supply and employment of qualified mathematics and science teachers has not only more than kept pace with increases in mathematics and science student enrollments, but also with mathematics and science teacher retirement increases-a point we address in Trend 2.…”
Section: Trend 1: Largermentioning
confidence: 77%
See 1 more Smart Citation
“…This premise is flawed for a number of reasons. To begin with, there is a shortage of strong mathematics teachers in urban schools (Ingersoll & Perda, 2010), an issue that cumulatively limits many children's learning opportunities year after year. Even beyond school staffing challenges, technical issues abound in the measures themselves.…”
Section: What the How Of Nclb Specifies: Educational Inequality As A mentioning
confidence: 99%
“…All but four of the teachers had earned a bachelor's degree as their highest level of education; three of these four teachers had earned master's degrees, and one teacher had a doctoral degree. As Ingersoll and Perda (2010) identified in their research, several teachers who participated in the study entered teaching mid-career. Eight participating teachers had careers outside of education prior to teaching mathematics in the middle grades.…”
Section: Setting/participantsmentioning
confidence: 99%